The concept of the Polish Biographical Dictionary: its history and editorial issues - Agata Barzycka-Paździor (Studia Lexicographica)
The aim of the article is to present a concept of the Polish Biographical Dictionary (Polski Słownik Biograficzny, PSB), which has been published in Krakow since 1935 as a multi-volume publication of the Polish Academy of Sciences (PAN) and the Polish Academy of Arts and Sciences (PAU), and realised by the Tadeusz Manteuffel Institute of History of the PAN. Over 28,000 biographies of people associated with Poland (and with the Grand Duchy of Lithuania, the Commonwealth of Both Nations, and their fiefs), who lived or operated in the country and abroad from the time of legendary Duke Popiel (9th century) to 2000, have been published in 52 volumes so far. The concept of the PSB is presented in the historiographic context as well as the context of contemporary problems and challenges that the PSB is facing.